2016
DOI: 10.3139/124.110564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the wallpaper fuel design on the neutronic behavior of the HTR-10

Abstract: TRISO-wrapped fuel particle failure is a function of local temperature. The spherical symmetry and hence central temperature peak in PBM-type reactor fuel pebbles can lead to considerably higher failure rates at the center of the pebbles. The so-called “wallpaper fuel” concept has been shown to be a viable solution to this issue. In this paper, the neutronic aspects of this modification were studied using MCNP. According to the obtained results, the inclusion of a central fuel-free zone could lead to a more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…The structural components of the reactor core such as graphite reflectors were easily modeled while the coolant in the reflector side and especially, the reactor shutdown and control systems require special effort in modeling. The modeling and calculations performed in this study were demonstrated successfully in various publications [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Pebbles In Core Modelingmentioning
confidence: 76%
“…Core com po nents and struc tures, such as ax ial and ra dial re flec tors, etc., were mod eled in a sim pler way. A de tailed de scrip tion of this pro ce dure was first in troduced by Lebenhaft [19] and found in sev eral pub li cations [20][21][22][23][24][25][26][27][28]. The whole fa cil ity mod el ing of HTR-Proteus is il lus trated in fig.…”
Section: Cal Cu La Tion Modelmentioning
confidence: 99%
“…The graphite reflector and other reactor geometry, such as carbon layer around the system, helium channels and control rods, were modelled in detail and comprehensively. The modelling procedure in this study was first developed by Lebenhaft [16] and utilized in some publications [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Figure 4 illustrates the MCNP6 model for the second heterogeneity of the pebble bed reactor.…”
Section: Fuel Kernelmentioning
confidence: 99%